ANGKA KEJADIAN DAN KARAKTERISTIK PASIEN EMBOLI PARU PADA PASIEN CORONAVIRUS DISEASE-19 (COVID-19): SYSTEMATIC REVIEW - Haura Amanda Rifky, (2021)
At the end of 2019, WHO received a warning towards the occurrence of pneumonia cases with unknown cause in Wuhan, China. After conducted isolation, it was identified that SARS-Cov-2 had caused pneumonia, then called Coronavirus Disease-19 (COVID-19). COVID-19 can cause various complications such as thrombotic complications with significant impacts on morbidity and mortality of patients. Therefore, this study aims to determine the incidence rate and characteristics of pulmonary embolism patients, one of the most common thrombotic complications in COVID-19 patients, using a systematic review method. A literature search was conducted from June to August 2020 using keywords "COVID-19 Pneumonia," "SARS-CoV-2," "Pulmonary Embolism," "thromboembolism," "thrombotic," "CT angiography," and then selected using the PRISMA-P method. It was obtained 23 studies met the inclusion and exclusion criteria. The literature was then conducted a quality assessment using Joanna Briggs Institute (JBI) criteria. In the studies conducted, the incidence rate of pulmonary embolism complications in COVID-19 patients is 23.7% (95% CI, 21.6-26%) with an average age of 59.2 years old. It was also obtained data that men are twice as likely to have pulmonary embolism complications than women. D-dimer and CRP levels are significantly increased, in which the mean of D-dimer is 9.76 µg/mL while CRP is 17.36 mg/dL with the most common type of embolism occurred is a peripheral type.